MWCNT induced negative real permittivity in a copolyester of Bisphenol-A with terephthalic and isophthalic acids - Ozdemir, Zeynep Guven; Dasdan, Dolunay Sakar; Kavak, Pelin; Pionteck, Juergen; Poetschke, Petra; Voit, Brigitte; Misirlioglu, Banu Sungu (IOP Publishing Ltd, 2020)
In the present study, the negative real permittivity behavior of a copolyester of bisphenol-A with terephthalic acid and isophthalic acid (PAr) containing 1.5 to 7.5 wt% multi-walled carbon nanotubes (MWCNTs) have been investigated in detail. The structural and morphological analysis of the melt-mixed composites was performed by Fourier transform infrared spectroscopy using attenuated total reflection (FTIR-ATR), atomic force microscopy (AFM), x-ray diffraction (XRD), and light microscopy. The influences of the MWCNT filler on the AC impedance, complex permittivity, and AC conductivity of the PAr polymer matrix were investigated at different operating temperatures varied between 296 K and 373 K. The transition from a negative to positive real permittivity was observed at different crossover frequencies depending on the MWCNT content of the composites whereas pure PAr showed positive values at all frequencies. The negative real permittivity characteristic of the composites was discussed in the context of Drude model.
Keywords: dielectric properties; composite; nanotubes; copolymers; ELECTRICAL-CONDUCTIVITY; DIELECTRIC-RELAXATION; THERMAL-PROPERTIES; NANOCOMPOSITES; SPECTROSCOPY; Materials Science